Gendered training and take home messages to improve pig husbandry in Uganda - Dione, Michel M. (International Livestock Research Institute, 2016)
About a year ago, Michel Dione started mainstreaming gender in his research on African swine fever. It is critical to assess gender dimensions in pig husbandry and disease control to better tailor interventions. Because women are deeply involved in pig husbandry, it made sense to make sure that women were involved in the study. The findings can help shape future interventions, approaches and policies. Interview with Michel Dione (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684